Design And Evaluation Of A Multimedia Program On Selected Daily Skills Among Children With Intelectual Disabilities In Al-Bahah, Saudi Arabia - Hanash A, Alghamdi Ahmed (2019)
Due to the lack of studies on developing life skills of children with intellectual disability in the Kingdom of Saudi Arabia (KSA), this mixed-methods study examined the effect of a multimedia program on the development four life-skills (self-care, health-care, avoiding environmental dangers and thinking skills) among children with intellectual disability in a centre for special education needs in AL-Bahah region in KSA. This study also examined perception of six teachers in the centre about the effectiveness of the multimedia program which was employed for one semester. The sample of the study included 44 children who were divided into two equal groups: experimental and control. The experimental group used the multimedia program, while the control group used the traditional way. At the end of the intervention, the respondents’ performance in the life-care skills were assessed using four observation cards; one for each skill. In addition, six teachers were interviewed regarding their perceptions of the effectiveness of the multimedia program.